Essential Oils Advances in Extractions and Biological Applications - Santana de Oliveira, Mozaniel; Helena de Aguiar Andrade, Eloisa (Biochemistry, 2022)
Over the years, natural products such as essential oils have been gaining more and more prominence due to their perceived health benefits. Plants rich in essential oils represent a viable source of biomolecules for use in the most varied human activities, such as agricultural, cosmetic, and pharmaceutical applications. Essential oils are natural volatile fractions extracted from aromatic plants that are formed by classes of substances such as fatty acid esters, mono and sesquiterpenes, phenylpropanoids, and aldehyde alcohols, and in some cases, aliphatic hydrocarbons, among others. In this context, this book includes twelve chapters that present new information on the extraction and application of essential oils in various industrial segments. It is divided into three sections that discuss the general concepts of essential oils and techniques for their extraction, topics in food science and technology, and essential oils and their pharmacological properties in various activities and applications.